(untitled) (Psicologia USP, 1993)
A reflexion on the research on the psychology of social memory is proposed, both from the point of view of general orientation and from that of individual tactics of investigation. The theoretical bases are Gestalt theory and the Bergsonian philosophy of time. The memorative processes are related to 'fields of significance' in the life of the subject who remembers. The influence of social groups on the formation of memories is discussed.